2009
DOI: 10.17221/950-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Evolution of Hydrophilic and Hydrophobic Peptide Contents in Cheeses Made from Ewe's Goat's or Cow's Milk

Abstract: Proteolysis is the principal and most complex biochemical event occurring during the maturation of the majority of ripened cheese varieties. In addition to softening the cheese body, proteolysis influences the development of cheese flavour via the formation of amino acid and peptides which make a direct contribution to flavour. Goat, cow and sheep cheeses have been elaborated with raw milk and calf rennet. The extent of proteolysis was monitored over six months of ripening and means of HPLC peptide profile ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In agreement with this, the summer cheeses in our trials were characterized by a higher content of vitamin A (Revilla et al, 2014). Moreover, previous works in similarly manufactured cheeses reported that summer cheeses had higher total contents of watersoluble peptides (Vivar-Quintana et al, 2009) and a lower fat content (González-Martín et al, 2011b). Although a positive correlation was observed between fat content and TEAC ( Figure 2) in our study, the fatty acid profile was affected by season-summer cheeses had a higher content of PUFA (2.85 vs. 2.33 g/100 g of fatty acids), which is, according to Lucas et al (2008a), positively correlated with antioxidant activity.…”
Section: Effects Of Animal Species Season and Ripeningsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with this, the summer cheeses in our trials were characterized by a higher content of vitamin A (Revilla et al, 2014). Moreover, previous works in similarly manufactured cheeses reported that summer cheeses had higher total contents of watersoluble peptides (Vivar-Quintana et al, 2009) and a lower fat content (González-Martín et al, 2011b). Although a positive correlation was observed between fat content and TEAC ( Figure 2) in our study, the fatty acid profile was affected by season-summer cheeses had a higher content of PUFA (2.85 vs. 2.33 g/100 g of fatty acids), which is, according to Lucas et al (2008a), positively correlated with antioxidant activity.…”
Section: Effects Of Animal Species Season and Ripeningsupporting
confidence: 90%
“…Examining the influence of seasonality on the ripening process showed that summer cheeses had lower hydrophobic:hydrophilic ratios than winter cheeses, especially after the first month of ripening, indicating strong proteolysis (results published in Vivar-Quintana et al, 2009). This is in agreement with reports of other authors and may be due, in part, to aminopeptidase activity of the lactic acid bacteria present in raw milk (Pérez-Elortondo et al, 1998;Mendia et al, 2000).…”
Section: Effects Of Animal Species Season and Ripeningsupporting
confidence: 87%
“…As indicated by various authors, seasonal changes in milk composition affect cheese yield and quality,1, 13 the evolution of volatile components,3, 7, 14–17 free amino acid and free fatty acid contents18 and sensory characteristics 16, 19. Spring cheese might have more intense fruity and sweet overtones in comparison with winter cheese 46.…”
Section: Discussionmentioning
confidence: 97%
“…This is due to the change in animal feeding regimen, which directly affects the milk fatty acid profile 3. Furthermore, some authors found differences in proteolysis7, 14–17 and free amino acid contents7 due to seasonality. Since volatile components of cheese depend mainly on lipid and protein catabolism,7 the evolution of volatile components2, 4, 5, 9, 18, 19 is also affected.…”
Section: Introductionmentioning
confidence: 99%
“…buffalo milks are used (Vivar-Qüintana et al, 2009). Today, consumers' appetite for raw milk cheeses seems to be on the increase.…”
mentioning
confidence: 99%